ASSESSMENT OF HEMATOLOGICAL AND GROWTH RESPONSES OF HETEROBRANCHUS LONGIFILIS FINGERLINGS TO PROBIOTIC-SUPPLEMENTED DIETS - Abubakar, F.B.; Sani, I. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study assessed the hematological and growth responses of H. longifilis fingerlings fed diets supplemented with Aquapro, CHC, and their combination at 0.00%, 0.50%, 1.00%, and 1.50% inclusion levels for seven months. A total of 280 fingerlings (mean weight 5.3 ± 0.1 g) were distributed in a completely randomized design with triplicate treatments. Growth and hematological parameters were analyzed using standard methods. Results revealed that probiotic supplementation significantly (p < 0.05) enhanced growth performance and blood profiles compared to the control. Fish fed the combined probiotics at 1.50% inclusion achieved the highest final weight (348.79 ± 4.33 g) and specific growth rate (1.97 ± 0.41%), while the control recorded the lowest values (166.81 ± 2.37 g; 1.50 ± 0.00%). Feed conversion ratio improved from 1.95 in the control to 1.61 in probiotic-fed fish. Similarly, red blood cell count increased from 2.95 × 10⁶ mm⁻³ in the control to 4.01 × 10⁶ mm⁻³ in the combined probiotic group, while hemoglobin concentration rose from 10.17 ± 0.02 g/dL to 13.58 ± 0.20 g/dL. Packed cell volume also improved significantly from 33.00% to 35.80%. It was concluded that probiotic supplementation especially combined Aquapro + CHC diets at 1.0–1.5% significantly improved both hematological indices and growth performance in H. longifilis fingerlings. Such inclusion levels are therefore recommended to enhance productivity and physiological health in intensive aquaculture systems.